Acupuncture Alleviates CUMS-Induced Depression-Like Behaviors by Restoring Prefrontal Cortex Neuroplasticity - Peng Li; Wenya Huang; Yiping Chen; Muhammad Shahzad Aslam; Wenjing Cheng; Yang Huang; Wenjie Chen; Yanxun Huang; Xinnan Wu; Yining Yan; Junliang Shen; Tao Tong; et al. (Neural Plasticity)
Purpose. To explore the therapeutic efficiency of acupuncture and the related molecular mechanism of neural plasticity in depression. Methods. Chronic unpredictable mild stress- (CUMS-) induced rats were established for the depression animal model. There were a total of four rat groups, including the control group, the CUMS group, the CUMS+acupuncture group, and the CUMS+fluoxetine group. The acupuncture group and the fluoxetine group were given a 3-week treatment after the modeling intervention. The researcher performed the open-field, elevated plus maze, and sucrose preference tests to evaluate depressive behaviors. The number of nerve cells, dendrites’ length, and the prefrontal cortex’s spine density were detected using Golgi staining. The prefrontal cortex expression, such as BDNF, PSD95, SYN, and PKMZ protein, was detected using the western blot and RT-PCR. Results. Acupuncture could alleviate depressive-like behaviors and promote the recovery of the neural plasticity functions in the prefrontal cortex, showing the increasing cell numbers, prolonging the length of the dendrites, and enhancing the spine density. The neural plasticity-related proteins in the prefrontal cortex, including BDNF, PSD95, SYN, and PKMZ, were all downregulated in the CUMS-induced group; however, these effects could be partly reversed after being treated by acupuncture and fluoxetine (P<0.05). Conclusion. Acupuncture can ameliorate depressive-like behaviors by promoting the recovery of neural plasticity functions and neural plasticity-related protein upregulation in the prefrontal cortex of CUMS-induced depressed rats. Our study provides new insights into the antidepressant approach, and further studies are warranted to elucidate the mechanisms of acupuncture involved in depression treatment.